Strengthening small-scale farmers capability to enhance local food access amid disruptions - John Kibe Munyoro (Frontiers in Sustainable Food Systems)
This research reassesses the efficacy of long-term food systems and examines the strengthening of small-scale farmers capabilities through local skills development and education programs to enhance sustainable food accessibility during disruptions. Indigenous and local knowledge provides guidance on local resource management and innovation strategies, advancing local food systems transformation and adaptive capacities. A quantitative survey was conducted, reaching 1307 small-scale farmers across 47 Kenyan counties. Chi-square tests, linear regression, and crosstabulations were applied to analyze the relationship between skills development, education levels, farming practices, supply chain disruptions, food access, and technical skills transformation. The findings show that households with higher education levels are more resilient to supply chain disruptions, facilitating improved local food and market access. These results highlight the need for policies integrating indigenous and local knowledge, education, and skills development to strengthen local food systems transformation and stability, ultimately reducing dependence on short-term humanitarian aid.